Design of an Agile Methodology oriented to the development of software in dissertation projects - et. al., Gustavo Rivera, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The referred methodology is the result of a consistent research with the problems evidenced in the students' dissertations, who, when approaching software development projects, agree on the selection of agile methodologies inspired by the benefits evidenced by the market trend; finding themselves with the disjunctive of traversing academic spaces with substantial differences in relation to the business environment where the methodologies are generally aimed at. The conceptual framework of the proposed methodology is defined within the Software Engineering discipline, also related to the precepts attentive to agile methodologies and the academic approach to applicability. It has been experimented through case studies in the development of curricula of Higher Education in Engineering programs, where successful results have been observed. The most relevant characteristics of the methodology are based on the systemic approach of context, simplicity and ease of learning, and methodical components such as: iterative, incremental, collaborative work and adaptability to academic environments.